Role of Cognitive Radio on 4G Communications A Review - Kumar, Neeraj; Singla, Ayush (IJRDO -Journal of Computer Science Engineering, 2015)
There is a rapid advancement in wireless communication technology providing the network services anywhere andanytime. 4G communication systems are being developed to solve the various problems the current communicationsystems (3G, 2.5G) are facing.4G will be an intelligent technology that will reduce the number of differenttechnologies to a single global standard. Cognitive Radio (CR) is the key enabling technology for next generationnetworks. Cognitive Radio techniques provide the capability to use or share the spectrum in an opportunisticmanner. With the use of CR, 4G wireless networks will support global roaming across multiple wireless and mobilenetworks. In this paper, the Role of CR in 4G Communications is reviewed. The recent research being done onCognitive Radio and 4G technologies is identified. The main possibilities of implementing Cognitive Radios in 4GCommunication Systems are surveyed. IEEE 802.22 networks are cognitive technology based networks which willenhance the performance of 4G Communication systems. IEEE 802.16h (WiMAX) provide extensions to supportunlicensed coexistence. Keywords: Cognitive Radio (CR), WiMAX, 4th Generation (4G)